Rhinitis associated with asthma is distinct from rhinitis alone: The ARIA‐MeDALL hypothesis. Issue 5 (10th April 2023) - Bousquet, J.; Melén, E.; Haahtela, T.; Koppelman, G. H.; Togias, A.; Valenta, R.; Akdis, C. A.; Czarlewski, W.; Rothenberg, M.; Valiulis, A.; Wickman, M.; Akdis, M.; et al.
Abstract: Asthma, rhinitis, and atopic dermatitis (AD) are interrelated clinical phenotypes that partly overlap in the human interactome. The concept of "one‐airway‐one‐disease, " coined over 20 years ago, is a simplistic approach of the links between upper‐ and lower‐airway allergic diseases. With new data, it is time to reassess the concept. This article reviews (i) the clinical observations that led to Allergic Rhinitis and its Impact on Asthma (ARIA), (ii) new insights into polysensitization and multimorbidity, (iii) advances in mHealth for novel phenotype definitions, (iv) confirmation in canonical epidemiologic studies, (v) genomic findings, (vi) treatment approaches, and (vii) novel concepts on the onset of rhinitis and multimorbidity. One recent concept, bringing together upper‐ and lower‐airway allergic diseases with skin, gut, and neuropsychiatric multimorbidities, is the "Epithelial Barrier Hypothesis." This review determined that the "one‐airway‐one‐disease" concept does not always hold true and that several phenotypes of disease can be defined. These phenotypes include an extreme "allergic" (asthma) phenotype combining asthma, rhinitis, and conjunctivitis. Rhinitis alone and rhinitis and asthma multimorbidity represent two distinct diseases with the following differences: (i) genomic and transcriptomic background (Toll‐Like Receptors and IL‐17 for rhinitis alone as a local disease; IL‐33 and IL‐5 for allergic and non‐allergic multimorbidity as a systemic disease), (ii) allergen sensitization patterns (mono‐ or pauci‐sensitization versus polysensitization), (iii) severity of symptoms, and (iv) treatment response. In conclusion, rhinitis alone (local disease) and rhinitis with asthma multimorbidity (systemic disease) should be considered as two distinct diseases, possibly modulated by the microbiome, and may be a model for understanding the epidemics of chronic and autoimmune diseases.